Pengaruh Kemandirian dan Kedisiplinan Belajar terhadap Motivasi Belajar Mahasiswa Pasca Covid-19 - Bunga Dwi Wulan; Fatihah Fahmi Fidienillah; Anindya Citra Maharani Ariyadewi (Mathematics Education Study Program, 2025)
The COVID-19 pandemic has changed the dynamics of learning among students, posing new challenges in maintaining learning motivation. Independence and discipline in learning are crucial factors in dealing with this situation, especially in the context of higher education. The purpose of this study is to determine the influence of independence and learning discipline on the learning motivation of students of the Educational Technology Study Program, Sebelas Maret University. The research was conducted using a quantitative approach with a population of 106 students. Data was collected through a google form questionnaire distributed online regarding independence, discipline, and motivation to learn. The data obtained were analyzed using validity, reliability, normality and multiple linear regression with the help of SPSS software. This research refers to the theory of learning motivation and learning independence put forward by various experts. The findings of the study show that there is a positive and significant influence between independence and discipline on learning motivation, with an influence of 25.6% which shows the need to increase independence and discipline so that students are motivated to learn.